SEMIOTIC ANALYSIS OF SYMBOLS IN “THE MIDNIGHT LIBRARY” NOVEL - Sitti Fausiah; Muh Hasbi; Harnita Rosalia (Journal of English Literature and Linguistic Studies, 2026)
This study aims to analyzes the symbolism found in the library depicted Matt Haig's novel The Midnight Library. The purpose of this study is to identify and interpret the symbols that appear in the library. The method used is qualitative descriptive, with a focus on text data interpretation. Edward Sapir's (1934) classification of symbols was used to determine the types of symbols that  appear, while Charles Sanders Peirce’s semiotic approach was applied to understand the process of meaning formation through the relationship between representamen, object, and interpretant. The results of the study show that there are nine main symbols divided into referential symbols and condensation symbols. The referential has three symbols, those are The Book of Regrets, The Static Clock 00:00:00, and The Game of Chess. Where is condensation has six symbols, namely The Light, The Green Book, The Midnight Library, The Moving Shelves, Mrs. Elm, and Nora Seed. In terms of meaning, the referential symbols directly reflect Nora's experiences, choices, and regrets, while the condensation symbols combine various ideas and emotions, such as hope, uncertainty, the search for identity, and the potential for change. These findings confirm that the symbols in the library serve not only as narrative elements but also as semiotic devices that reveal the main character's existential struggles and process of self-reflection.